Guru Pancasila sebagai Figur Teladan dalam Pembentukan Sopan Santun Peserta Didik - Azhari, Fitriyah; Adhira, Meisya; Putri, Semila; Ramadhan, Galang Novian; Muhammad Arifin (CV. Kurnia Grup, 2025)
This study examines the role of Pancasila Education teachers as role models in shaping students’ courtesy at SMP Islam At-Taqwa. The research used a descriptive qualitative method through observations and interviews with teachers and eighth-grade students. The findings show that teachers instill social ethics through daily practices such as collective prayers, greeting rituals, and communal worship, accompanied by direct guidance and reprimands. Most students respond positively with respectful and polite behavior, although some still display inappropriate attitudes, such as being overly familiar with teachers and making noise during worship. Supporting factors include the school’s religious environment and consistent teacher role modeling, while obstacles arise from adolescence and external social influences. The study concludes that teachers play a crucial role in developing students’ social ethics.